Sisu [videorecording (DVD)] - Helander, Jalmari, 1976-; Lagerroos, Kjell; Virolainen, Juho; Seppä, Juri; Wäinölä, Tuomas; Tommila, Jorma, 1959-; Hennie, Aksel, 1975-; Doolan, Jack (Actor); Willamo, Mimosa; Tommila, Onni (Lionsgate, 2023)
During WWII, a solitary prospector crosses paths with Nazis in northern Finland. When the Nazis steal his gold, they quickly discover he is no ordinary miner. While there is no direct translation for the Finnish word "sisu," the legendary ex-commando will embody what it means: a white-knuckled form of courage and unimaginable determination in the face of overwhelming odds. And this one-man death squad will go to outrageous lengths to get his gold back even if it means killing every last Nazi in his path.